Customer perceptions towards innovation products in the sphere of privacy versus security debate (the case of transmission x-ray body scanners in the UK) - Zelenkevich, Marina; Zelenkevich, Leonid (Management and Administration Journal, 2025)
This article attempts to establish potential applications for widening the use of transmissionx-ray full body scanners in the United Kingdom (UK) as the product of innovation. It is the first researchproject of its kind and findings will be able to assist government agencies in enhancing currentsecurity systems within the transport and prison sectors of the UK. In addition, product manufacturerswill be able to adjust their marketing and product development strategies. The main findings of thisstudy demonstrated that introducing the product within the UK air transport and prison sectors couldenhance individual privacy. The product would also be able to combat the issue of contraband traffickingwithin the air transport and prison sectors of the UK to enhance security. It was, however, highlightedthat the product would not significantly improve staff and inmate safety within the prison sector.The issue of data security was also discussed and frequent travelers did not view the data producedby the product as being damaging to individual privacy, whilst a prison security manager viewed datasecurity as one of the most significant issues associated with widening the use of the equipment. Theresults also demonstrated that transmission x-ray full body scanners are not suitable to be used withinthe UK rail network as the equipment would cause major inconveniences for train passengers. Thenext section of this article will focus on discussing introduction of the innovation product in the sphereof the debate of privacy vs. security.